Assessing Tauhid-Driven Legal Sustainability for Community Justice: An Empirical Study of Indonesian Legal Experience - Sudiman Sihotang; Ilman Khairi; Marhaban Sigalingging (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2026)
The development of the modern legal system, which is moving towards positivism, has created a need for an approach that combines moral and spiritual dimensions to achieve justice. This study aims to evaluate the position of Tauhid as an epistemological foundation for sustainable legal development and to examine its application in the Indonesian legal system, incorporating an empirical sociological field study from Kampus Bertauhid Universitas Djuanda. The method employed is empirical sociological research combined with normative juridical analysis, utilising a philosophical and comparative approach. The findings indicate that Tauhid comprises three main epistemological dimensions: ontological, axiological, and praxeological, which serve as the foundation for creating a just legal system. The integration of monotheistic values has begun to be applied in several areas of national law, particularly in family law and Islamic economics, although it is still not evenly distributed across all legal aspects. This study develops a model of Sustainable Integrated Tauhidic Justice (STIJ), encompassing substantive, procedural, institutional, and cultural dimensions as a comprehensive analytical framework. The empirical study demonstrates that a legal approach based on Tauhid significantly strengthens inclusive and sustainable social justice within the Indonesian legal framework, particularly when supported by campus-based community awareness.